2007
DOI: 10.1152/ajpcell.00518.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ATP, Mg2+, and redox agents on the Ca2+ dependence of RyR channels from rat brain cortex

Abstract: Despite their relevance for neuronal Ca(2+)-induced Ca(2+) release (CICR), activation by Ca(2+) of ryanodine receptor (RyR) channels of brain endoplasmic reticulum at the [ATP], [Mg(2+)], and redox conditions present in neurons has not been reported. Here, we studied the effects of varying cis-(cytoplasmic) free ATP concentration ([ATP]), [Mg(2+)], and RyR redox state on the Ca(2+) dependence of endoplasmic reticulum RyR channels from rat brain cortex. At pCa 4.9 and 0.5 mM adenylylimidodiphosphate (AMP-PNP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 67 publications
3
24
1
1
Order By: Relevance
“…9C). The frequencies of emergence of the three responses to Ca 2ϩ after fusion of ER isolated with DTT (77, 22, and 1% for low, moderate, and high activity channels, respectively) (Bull et al, 2007) differs from the frequencies found here with control ER isolated using physiological GSH/GSSG ratios ( p ϭ 0.02). The very low endogenous levels of S-glutathionylation and/or S-nitrosylation displayed by the RyR isoforms present in ER isolated with DTT may underlie their lower degree Single RyR channels recorded after fusion of ER vesicles obtained from control or ischemic brains and of ER vesicles from control brains preincubated with NADPH or NOR-3.…”
Section: Sh Modification Of Cortical Ryr Isoformscontrasting
confidence: 88%
See 3 more Smart Citations
“…9C). The frequencies of emergence of the three responses to Ca 2ϩ after fusion of ER isolated with DTT (77, 22, and 1% for low, moderate, and high activity channels, respectively) (Bull et al, 2007) differs from the frequencies found here with control ER isolated using physiological GSH/GSSG ratios ( p ϭ 0.02). The very low endogenous levels of S-glutathionylation and/or S-nitrosylation displayed by the RyR isoforms present in ER isolated with DTT may underlie their lower degree Single RyR channels recorded after fusion of ER vesicles obtained from control or ischemic brains and of ER vesicles from control brains preincubated with NADPH or NOR-3.…”
Section: Sh Modification Of Cortical Ryr Isoformscontrasting
confidence: 88%
“…After incubation, the brain cortex was quickly dissected and homogenized at 4°C. Total and reduced glutathione were measured, and the GSH/GSSG ratio was calculated (see Materials and Methods (Marengo et al, 1996;Bull et al, 2003Bull et al, , 2007. Because low and moderate activity channels gated with fast kinetics between closed and open states, P o values (denoted as P o *) were calculated as the ratio between the mean current of the entire channel recording and the single-channel current amplitude measured in longlasting (Ͼ30 ms) fully open events (Bull et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…De otro lado, recientemente se ha descrito la importancia de los canales de calcio intracitoplasmáticos de neuronas, células cerebelosas y células endoteliales capilares cerebrales (las mismas que conforman la barrera hemato-encefálica) de ratones, en el proceso de diferenciación neuronal y progresión de la neurogénesis ( 73,74 ). Precisamente, la activación de dichos canales está mediada por la oxidación coordinada de radicales SH, sobre los cuales el timerosal ejerce un potente efecto modulador, incrementando las concentraciones de calcio intracitoplasmático; de esta manera, se ha señalado que este último puede alterar la fisiología de las células nerviosas, gracias a sus efectos sobre el estado de óxido-reducción, conduciendo a trastornos funcionales, depleción de glutatión y aumento del estrés oxidativo ( [75][76][77][78][79] ).…”
Section: Resultsunclassified